Tracked Changes. Clinical laboratory testing and in vitro diagnostic test systems. Susceptibility testing of infectious agents and evaluation of performance of antimicrobial susceptibility test devices. Evaluation of performance of antimicrobial susceptibility test devices against reference broth micro-dilution Part 2, (1st February 2022) - British Standards Institution,
No abstract available